Consumption smoothing in Mexico over the life-cycle and the business cycle - Barbosa Rangel, Erika (2017)
This thesis examines household consumption behaviour over the life-cycle and the business cycle, using three rich Mexican datasets and several microeconometric techniques. The three chapters study how consumption is affected by: i) retirement; ii) intergenerational transfers; and iii) aggregate dynamics.